Design of a fuzzy-labview-based mechanical ventilator - Guler, Hasan; Ata, Fikret (C R L Publishing Ltd, 2014)
The purpose of the present study is to design a fuzzy-based mechanical ventilator and obtain respiration waveforms. An intelligent model for the mechanical ventilator was firstly developed in Matlab/Simulink after which a fuzzy-LabVIEW based mechanical ventilator prototype was practically designed. A fuzzy logic controller was used independently for both the simulation and experimental setup. In the simulation, three linear lung models namely the simple one-compartment, series two-compartment and parallel two-compartment models have been used to represent the lung. Inspiration and expiration times were estimated using the implemented Simulink model. Secondly, a fuzzy-LabVIEW based mechanical ventilator prototype was designed and estimation of inspiration/expiration time was made using 8 female Wistar Albino rats. It is seen that when lung resistance, R, increased in the simulation and the experiments, the inspiration time and pressure in the lung increased just like in practice. In addition to this, it can be said that irregular respiration rates do not create any problems in the ventilation of rats.
Keywords: Fuzzy Logic; LabVIEW; Mechanical Ventilator; Respiration; Lung Mechanics